Political Holes in the Economy: The Business Network of Partisan Firms in Hungary - David Stark; Balazs Vedres (Journal of Economic Sociology, 2012)
Research on interactions between business and politics indicates that business ties are a predictor of political behavior. This paper redirects attention from the question of how business ties have an impact on politics to the question of how political ties have an impact on business. Specifically, do divisions within the field of politics become divisions in the field of business networks? To study the co-evolution of the political and economic fields, we conduct an historical network analysis of the relationship between firm-to-party ties and firm-to-firm ties in Hungarian economy. We construct a data set of all senior managers and boards of directors of the largest 1696 corporations and the complete set of all political officeholders from 1987 to 2001. The findings of our field interviews and dyadic logistic regression models demonstrate that director interlocks depend, to a significant extent, on political affiliations. Although the economic and political fields have been institutionally separated, firms and parties have become organizationally entangled. Firms of either left or right political affiliation exhibit a preference for partnerships with firms in the same political camp while increasingly avoiding ties with firms in the opposite camp. Our historical analysis demonstrates that political camps in the Hungarian economy occur not as a direct legacy of state socialism but as the product of electoral party competition.